Schaum's Outline of Linear Algebra - Lipschutz, Seymour; Lipson, Marc Lars (New Delhi: McGraw Hill Education, 2001)
This third edition of the successful outline in linear algebra--which sold more than 400,000 copies in its past two editions--has been thoroughly updated to increase its applicability to the fields in which linear algebra is now essential: computer science, engineering, mathematics, physics, and quantitative analysis. Revised coverage includes new problems relevant to computer science and a revised chapter on linear equations.
Appendix 415-419p.; List of symbols 420p.; Index 421-424p.
Keywords: Canonical forms; Diagonalization; Linear mapping; Vector spaces